Application of the Game Based Learning Model to Improve Students' Concept Understanding Ability at SMP Negeri 35 Medan - Charral Erikson Sipahutar; Mukhtar (Formosa Journal of Science and Technology, 2023)
The purpose of this study was to determine the effect of applying a game-based learning model that can improve students' ability to understand mathematical concepts in the matter of number patterns at SMP Negeri 35 Medan. The type of research is classroom action research with 32 students in class VIII-5 SMP Negeri 35 Medan as subjects. From the data analysis, in the first cycle, 18 students (64.28%) achieved completeness, while 14 students (35.72%) did not complete it with an average grade of 73.66. In cycle II, students who had achieved mastery increased to 24 students (85.71%) while 8 students (14.29%) had not completed with an average grade of 86.38. So it can be concluded that the ability to understand mathematical concepts of SMP Negeri 35 Medan students increased by applying the game-based learning model.